The possibility of using TiO2 Nanotube Arrays‏ ‏as an adsorbent for removing lead ions ‎from aqueous solutions - Abood, Methaq I.; Al-Abdullah, Zainab T. Y. (Mesopotamian Journal of Marine Sciences, 2023)
This work focused on the elimination of lead ions from aqueous solutions using titanium dioxide nanotubes synthesised by anodization method as an adsorbent material using the batch system. The prepared titanium dioxide tubes(TNTs) were characterized using a scanning electron microscope device(SEM). The prepared tubes were within the nanoscale. Various conditions affected the adsorption process were studied, such as equilibrium time, temperature, acidity function and initial concentration of lead ions. It was found that the highest removal percentage occurred at the pH = 8 and that the time required for system equilibrium was 60 minutes. It was also found that the removal percentage increases with increasing temperature, which indicates the adsorption reaction as an endothermic. The Langmuir and Freundlich adsorption isotherms were also studied. The Freundlich equation was the most appropriate to the studied system. The thermodynamic studies also exhibited that the removal process was spontaneous, and the ΔS positive values ​​indicated randomness increasing.